Effect of water ageing on fatigue damage of rubberwood/recycled polypropylene composites - Nordin, Mohd Nur Azmi; Mustafa, Zaleha; Ratanawilai, T. (2023)
In this work, tension-tension fatigue performances of rubberwood flour reinforced recycled polypropylene composite (RWPC) under constant amplitude sinusoidal load control at 60% UTS, frequency of 4 Hz, R = 0.1, and at room temperature were investigated for unaged composite and after exposure to the water ageing conditions. From this series of tests, the corresponding stress-strain was obtained. The hysteresis loops throughout fatigue testing were examined, and the variation of secant modulus per cycle throughout the specimen lifetime was quantified. It was demonstrated that exposure to moisture reduced the initial tensile strength from 26.33 MPa to 12.19 MPa. Consequently, the fatigue strength of the RWPC also reduced from 630,030 cycles to 406,932 cycles as a consequence of the water ageing. The fatigue hysteresis loop showed that the non-ageing composite has a more open area and extensive tensile creep and more extensive fatigue damage compared to the aged composite as a result of their higher fatigue strength.